Implementacja najlepszych praktyk w rachunkowości zarządczej - Kowalak, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents the use of best practices in management accounting of companies. It presents methods of the search, implementing, and correcting practices used by companies. The author pays attention to risks that can appear during implementing best practices. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 63-69